Disparitas Kualitas Sumber Daya Manusia di 35 kabupaten dan kota di Propinsi Jawa Tengah - Supadi Supadi; Hary Pudjianto (EKO-REGIONAL, 2011)
Human development has been realized in many countries as one of objective goals to achieve national economic welfare. The problems that face on majority states were the disparities of their human development quality. On Central Java study case, with Human Development Index to count human quality development goal, this research found some indicators to reduce the disparity. Indirectly, the quality of the human development should be increased properly by pushed the local economies performance, basic education level facility, low of infrastructure damage, and also public involved on modern economic activity. Also, the difference of city and regency type that proved statistically had important effect on human development performance. Other factors that affected positively to human development quality were labor availability, industrial concentration, and health facility. This research also founded that the advancement of human development quality correlated positively to per capita income and decreasing of poverty. Keywords: human development quality, central java, poverty